High‐Performance All‐Solid‐State Batteries Enabled by Intimate Interfacial Contact Between the Cathode and Sulfide‐Based Solid Electrolytes. (16th January 2023) - Kim, Jeongheon; Kim, Min Ji; Kim, Jaeik; Lee, Jin Woong; Park, Joonhyeok; Wang, Sung Eun; Lee, Seungwoo; Kang, Yun Chan; Paik, Ungyu; Jung, Dae Soo; Song, Taeseup
Abstract: All‐solid‐state batteries (ASSBs) are considered the ultimate next‐generation rechargeable batteries due to their high safety and energy density. However, poor Li‐ion kinetics caused by the inhomogeneous distribution of the solid electrolytes (SEs) and complex chemo‐mechanical behaviors lead to poor electrochemical properties. In this study, LiNi0.8 Co0.1 Mn0.1 O2 (NCM) (core) – Li6 PS5 Cl (LPSCl) SEs (shell) particles (NCM@LPSCl) are prepared by a facile mechano‐fusion method to improve the electrochemical properties and increase the energy density of ASSBs. The conformally coated thin SEs layer on the surface of NCM enables homogeneous distribution of SEs in overall electrode and intimate physical contact with cathode material even under volume change of cathode material during cycling, which leads to the improvement in Li‐ion kinetics without the increase in solid electrolyte content. As a result, an ASSBs employing NCM@LPSCl with 4 mAh cm −1 specific areal capacity exhibits robust electrochemical properties, including the improved reversible capacity (163.1 mAh g −1 ), cycle performance (90.0% after 100 cycles), and rate capability (discharge capacity of 152.69, 133.80, and 100.97 mAh g −1 at 0.1, 0.2, and 0.5 C). Notably, ASSBs employing NCM@LPSCl composite show reliable electrochemical properties with a high weight fraction of NCM (87.3 wt%) in the cathode. Abstract : The solid electrolytes coated LiNi0.8 Co0.1 Mn0.1 O2 (NCM) particles are prepared by a facile mechano‐fusion method for the all‐solid‐state battery with high energy density. The conformally coated layer on the NCM enables homogeneous distribution of solid electrolytes in electrode and intimate contact with NCM during cycling, which leads to the improvement in Li‐ion kinetics without the increase in solid electrolyte content.